Application features of the cone-beam computerized tomography method in endodontic practice (LLC "Endo Press", 2020)
Article is devoted to studying of informational content of a cone-beam computerized tomography and periapical radiography analysis in the course of planning and carrying out endodontics treatment of teeth. The analysis of scientific data and clinical supervision revealed advantages of a cone-beam computerized tomography in comparison with traditional methods of visualization. Recommendations for improvement of quality of radiodiagnosis when planning treatment of root canals of teeth are made